PSYCHOHYGIENIC ASPECTS OF CREATING A PREVENTIVE ENVIRONMENT IN A MODERN HIGHER EDUCATIONAL INSTITUTION: PROBLEMS AND PROSPECTS - Serheta , Ihor (Collection of scientific papers «ΛΌГOΣ», 2022)
Modern students are a special contingent in the composition of the population, the state of health of which is a sensitive barometer of the social well-being of society and the level of adequacy of medical care of the population. The analysis of the interrelationship of the quality of life of students, which is related to their state of health, as well as individual factors that shape a certain way of life, provides an opportunity to note the priority areas of effective improvement of student youth, namely: measures for the formation of positive cognitive activity, rational organization of the educational process and free time, the formation of the foundations of a healthy lifestyle of student youth, and also, taking into account the fact that the influence of the educational space in which students spend most of their time causes changes in the adaptation potential of the organism, the leading features of which are stressing the mechanisms of adaptation and the formation of prerequisites for the deterioration of students’ health, measures aimed at increasing the psychophysiological, mental and social-psychological adaptation of young women and young men [1, 2, 3]. Therefore, only a thorough analysis of psychological-pedagogical and psychohygienic problems of professional training of students, and, first of all, consideration of existing teaching methods and the search for new science-based approaches to the optimization of educational activities, provide an opportunity to ensure the activation of the educational process, to make a probabilistic prediction of the level of professional training in the future, to create a preventive environment in a modern higher education institution [4, 5].